Protein interactions with corroding metal surfaces: Comparison of Mg and Fe - Wagener, Victoria; Faltz, Anne-Sophie; Killian, Manuela; Schmuki, Patrik; Virtanen, Sannakaisa (Faraday Discussions, 2015)
The influence of bovine serum albumin (BSA) on the electrochemical behaviour of pure Mg and Fe was studied in simulated body fluid (SBF), in view of the possible application of these materials as biodegradable metals. Results indicate a different trend for the BSA-effect on corrosion for the two metals: for Mg, a strong corrosion-inhibiting effect is observed in the presence of BSA in solution, especially for short-term exposure, whereas for Fe only a slight acceleration of corrosion is caused by the addition of BSA to the solution. For both metals, the protein-effect on the electrochemical behaviour shows a complex time-dependence. Surface analysis indicates that stronger BSA adsorption takes place on Mg than on Fe. Moreover, adsorption experiments with BSA and a second protein (lysozyme) were conducted. The results are discussed in view of electrostatic interactions between differently charged metal oxide/hydroxide surfaces and proteins.